MADRASAH HEAD MANAGERIAL LEADERSHIP IN IMPROVING TEACHER PERFORMANCE AT MI ASSA'IDIYYAH CIPANAS CIANJUR - Ina Nurul Inayah; Mulyawan Safwandy Nugraha (Media Inovasi Pendidikan dan Publikasi, 2023)
The madrasah principal's style, method, and managerial abilities in his capacity as a leader are very important for success in improving teacher performance under his leadership. The purpose of this study was to reveal in depth the managerial leadership style of the Ibtidaiyyah Assa'idiyyah Cipanas Cianjur madrasa principal in improving teacher performance. This research is a qualitative field research that is a descriptive case study in nature. Methods of data collection using in-depth observation, in-depth interviews, and documentation. Data analysis was carried out starting from data reduction, data presentation, and drawing conclusions. Extended attendance, triangulation, peer discussions, and clarification with informants were carried out to test the validity of the data. The study results show that the madrasah head's planning to build the character of teacher performance at MI Assa'idiyyah Cipanas Cianjur.